Analisis Pengaruh Kebijakan Hutang Dan Kebijakan Dividen Terhadap Kinerja Keuangan Pada Sektor Otomotif Yang Terdaftar di Bei Periode 2020-2022 - Al-Farisi, Muhammad Salman; Sulistyowati, Ari; Indriani, Bonita Revana; Sefianggraini, Diah Ayu; Rahmadani, Rina (Jurnal Ilmiah Wahana Pendidikan, 2024)
The purpose of this study is to identify and investigate the impact of debt policy and dividend policy on the financial performance of automotive enterprises. The method used is quantitative and data is collected from his IDX website, scientific publications and the internet. The population of this study consists of companies in the automotive industry listed on IDX for the period 2020-2022, based on a sample of three companies. The data analysis techniques used are descriptive statistical analysis, multiple regression analysis, t-hypothesis and f-hypothesis testing to detect partial and simultaneous effects. As a result, the debt policy variable partially has a negative and significant effect on financial performance, while the dividend policy variable has a negative and insignificant effect on financial performance. At the same time, the two variables did not have a significant impact on financial performance.